English Language Learning Achievement in Public Middle-School 1 Kertanegara: The Effects of "Jigsaw" Method - Masruroh, Yulfah; Fatmasari, Elly; Iskandar, Iskandar (ETDC: Indonesian Journal of Research and Educational Review, 2022)
The purpose of this action research is to learn about the improvement of English learning achievement for descriptive text using the Jigsaw method in the seventh grade at Public Middle-School 1 Kertanegara. This type of research uses classroom action research. The researcher's subjects are 32 students from Class F of Public Middle-School 1 Kertanegara. The study design consists of planning, implementation, observation, and reflection. Data collection methods used are observation, test, non-test, and interview. The result of the study conducted by researchers proved that the Jigsaw method was able to improve learning achievement for descriptive texts. During the observation, there was a significant increase in mastery learning at 75% in the first cycle and 84% in the second cycle. At the beginning of the action, there were 17 students who completed it; in the first cycle, that number increased to 24 students, and in the second cycle, it increased to 27 students. Based on the comparison of the number of students’ learning achievements, there is an increase in learning achievement through the Jigsaw method. From this description, it can be concluded that students’ learning achievement for descriptive text can be improved through the Jigsaw method.